Ensuring employment and labor of persons with disabilities (International conference on multidisciplinary science, 2023)
The development of each country is largely determined by the level of use of professional, intellectual and creative abilities of people. Including all categories of unemployed citizens (youth, disabled, women, people of retirement age, etc.) is of primary importance. The labor market is understood as a system that includes a complex of social and labor relations related to the terms of hiring labor, its use and exchange for living, its self-realization features, and the supply and demand mechanism.